2019
DOI: 10.1080/1331677x.2018.1561320
|View full text |Cite
|
Sign up to set email alerts
|

Poverty and trade liberalization: empirical evidence from 21 African countries

Abstract: The study investigated the possible nexus between trade liberalization and poverty in 21 African countries covering the period 2005-2014. The study deployed the following econometric tests: descriptive statistics; the correlation matrix and variance inflator; the panel unit root test; the pooled OLS technique; and the panel co-integration test (Johansen co-integration test). In order to confirm the robustness and validity of the regression model result, Ramsey RESET, cross dependence, autocorrelation and heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
25
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 38 publications
7
25
0
4
Order By: Relevance
“…In particular, information flows and more liberal trade restrictions robustly relate to lower poverty. The results also corroborate those of Koffi et al (2018), which found that trade reduced poverty level in Indonesia, as well as those of Salimi et al (2014), Keho (2017), Sokang (2018), Ali et al (2018), Gnangnon (2019), and Onakoya et al (2019). Employment rate and population growth rate reduced economic growth in both the short and long runs.…”
Section: Robustness Checksupporting
confidence: 89%
See 1 more Smart Citation
“…In particular, information flows and more liberal trade restrictions robustly relate to lower poverty. The results also corroborate those of Koffi et al (2018), which found that trade reduced poverty level in Indonesia, as well as those of Salimi et al (2014), Keho (2017), Sokang (2018), Ali et al (2018), Gnangnon (2019), and Onakoya et al (2019). Employment rate and population growth rate reduced economic growth in both the short and long runs.…”
Section: Robustness Checksupporting
confidence: 89%
“…The author employed the Two Stage Least Square (2SLS) method and showed that trade openness increased economic growth and led to poverty reduction but increased income inequality in the country. Onakoya et al (2019) employed pooled Ordinary Least Square (OLS) to investigate the impact of trade liberalisation on poverty in 21 African countries. The study covered the period between 2005 and 2014 and revealed that trade reduced poverty level in these countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The long-run result is contrary to expected sign and finding of Giles and Williams (2000), who show that an increase in trade can increase exports, which come with increased incomes and hence higher consumption. However, it is in line with the findings of Magombeyi and Odhiambo (2017), Onakoya et al (2019). The negative relationship could be due to several reasons.…”
Section: Discussion Of the Empirical Results On The Relationship Betwsupporting
confidence: 91%
“…They found that openness to trade reduces infant mortality rate and increases expectancy for both men and women in the region. Onakoya et al (2019) investigated the link between trade liberalization and poverty in 21 African countries from 2005 to 2014. Using both the pooled OLS technique and the panel cointegration test, they found a negative and significant relationship between trade openness and poverty.…”
Section: Empirical Literaturementioning
confidence: 99%
“…Le Goff and Singh (2014) study using data for the period 1981 to 2010 showed that the effects of trade on poverty in Africa was not automatic; deep financial markets, high education levels, and strong institutions are required. A more recent study, Onakoya et al (2019), using data for 2005 to 2014, found a negative relationship between trade and poverty, measured as HDI. In other words, trade actually increased the level of poverty in the period studied.…”
Section: Foreign Tradementioning
confidence: 97%